DEVELOPMENT OF VILLAGE OWNED BUSINESS ENTITY GOVERNANCE MODEL - Budi Hendaris, Raden; Siraz, Rahmat (Dinasti International Journal of Management Science, 2021)
Village Owned Enterprises (Bumdes) must be able to support the village's economy while also assisting in the resolution of social issues in the Bumdes environment. However, not all Bumdes are capable of maintaining the village economy and overcoming social issues in its implementation. As a result, there was a management mistake that led Bumdes to stop working properly. The goal of this research was to determine the impact of governance on Bumde's performance. A questionnaire was sent to Bumde's management in West Bandung Regency, with a sample size of 117 Bumdes. Initial surveys, the creation of concepts and equipment, data gathering, and data analysis are all part of the research phase. Smart PLS version 3.0 software was used to analyze the data. Transparency, accountability, participation, emancipation, and sustainability were found to have a substantial impact on performance, but cooperative had no effect.